Desenvolvimento de um protótipo detector para avaliar parâmetros de qualidade do equipamento de raios X convencional - Murata, Camila Hitomi [UNIFESP] (2016)
Medical radiological equipment must operate in compliance with the performance standards specified by ANVISA and the Ministry of Health. Periodic checks of the performance of these equipment are necessary to maintain the safety of the medical procedure and guarantee the quality of the images. The instrumentation used in these verifications is specific, of high cost and is not available in the national market. Aim: to develop a multifunctional prototype and study the response of its detection system in the evaluation of peak voltage value, practical peak voltage, exposure time, semi- Radiation dose and dose rate. Method: A prototype plate with 4 PIN RD100A solid state sensors and a multifunctional X-ray beam analysis system were used. The reproducibility and accuracy tests of the measurements presented by the prototype were initially performed with radiological equipment dedicated to research and compared to Commercial detectors (Article 1). In continuity (Article 2) the algorithms for obtaining response curves and Complementary functions that met the normative requirements for radiological equipment. New tests were carried out in accredited laboratories and internationally certified. Results: The prototype presents voltage measurements (kV) between 50-150 kV with accuracy between 0.03 and 1.53%, according to international regulations. For time measurements it meets the following specifications: 0.001-1s with accuracy of ?1ms and resolution of 0.1ms. Conclusion: The results of the Calibration demonstrates that the prototype has the requirements of a functional instrument capable of evaluating the performance of radiological equipment with a single exposure.